2013
DOI: 10.1186/1746-1596-8-90
|View full text |Cite
|
Sign up to set email alerts
|

Solitary myofibroma of the sigmoid colon: case report and review of the literature

Abstract: A 58-year-old woman presented with a solitary myofibroma that arose in the sigmoid colon. Computed tomography revealed a highly enhanced intramural mass (1.3-cm maximum diameter) in the proximal sigmoid colon. Histologically, the tumor exhibited a biphasic growth pattern, which comprised haphazardly arranged, interwoven fascicles of plump, myoid-appearing spindle cells with elongated nuclei and abundant eosinophilic cytoplasm, and more cellular areas of primitive-appearing polygonal cells that were arranged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Mitoses are variable in number; especially in immature-appearing tumors, numerous mitoses as well as areas of necrosis may be present 4. Myofibroma should be differentiated from leiomyoma, neurofibroma, nodular fasciitis, hemangiopericytoma, and fibrosarcoma due to their macroscopic and microscopic similarites 2,6,10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitoses are variable in number; especially in immature-appearing tumors, numerous mitoses as well as areas of necrosis may be present 4. Myofibroma should be differentiated from leiomyoma, neurofibroma, nodular fasciitis, hemangiopericytoma, and fibrosarcoma due to their macroscopic and microscopic similarites 2,6,10…”
Section: Discussionmentioning
confidence: 99%
“…Both forms were described as infantile myofibromatosis because of its multiplicity, typical age distribution (first decade of life), and frequent involvement of deep structures, including the central nervous system and visceral organs such as lung, heart, gastrointestinal tract, liver, kidney, and pancreas 1. In contrast to the multicentric form, solitary myofibroma usually presents as a cutaneous or subcutaneous mass of the head and neck region 2. Intraosseous lesions are much less common, although three studies in 1995 and one in 2000 reported the mandible as a frequent oral site (16 of 36 [or 44%],3 15 of 35 [or 42.6%],4 and 30 of 79 [or 38.0%]) 5.…”
mentioning
confidence: 99%
“…They usually arise de novo and are seen in adults [6]. Myofibroma can occur as a solitary form or it can be seen as multiple lesions like generalized form which is described as myofibromatozis [2,7]. It is originally described as 'congenital generalized fibromyomatosis' in 1954 by Stout [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent tumors are Gastrointestinal Stromal Tumors (GIST) and smooth muscle tumors. GISTs as the largest group of these tumors are usually seen in the wall of gastrointestinal tract and 25% of them are malignant [2] . They usually occur in adults and there is no sexual predominance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation